Analisis Kepuasan Kerja dan Motivasi Kerja Terhadap Disiplin Kerja Karyawan (Studi Kasus: Puskesmas Kadugede Kuningan Jawa Barat) - Rani Kurniasari; Ikhsan Maulana (Universitas Bina Sarana Informatika, 2019)
Employees as human resources in the company need to be managed properly. By providing high job satisfaction, it is expected that employees will voluntarily work with good work discipline. This research was conducted to find out job satisfaction with employee work discipline at the Kadugede Kuningan Health Center, West Java. The author uses the SPSS (Statistical Product and Service Salutions) application to calculate the regression equation test, and ANOVA with an error rate of 5% or 0.05. The entire population as a sample is saturated sampling using a Likert Scale. Based on the calculation of 48 respondents on the distribution of the questionnaire, the correlation coefficient value of 0.482 means that job satisfaction and work motivation on work discipline have a strong influence. Job satisfaction and work motivation contributed 48.2% to the occurrence of work discipline, and 51.8% was influenced by other variables outside this study. The results of the regression equation Y Y = 10.068 + 0.526X1 + 0.257X2 + e. If X = 0, the value of work discipline is 10,068 or without being influenced by job satisfaction and work motivation. Keywords: Job satisfaction, Work motivation, Work discipline